Caveolin-1 Promoted Collateral Vessel Formation in Patients With Moyamoya Disease - Zhao, Jinbing; Yu, Zhiqiang; Zhang, Yanping; Qiu, Cheng; Zhang, Guangxu; Chen, Lijiu; He, Shengxue; Ma, Jun (Frontiers in Neurology, 2022)
Background：Caveolin-1 (Cav-1) plays pivotal roles in the endothelial function and angiogenesis post ischemia. Moyamoya disease (MMD) is characterized by progressive artery stenosis with unknown etiology. We aim to determine whether serum Cav-1 levels of MMD patients were associated with collateral vessel formation after bypass surgery. Methods：We studied serum Cav-1 levels of 130 MMD patients (16 with RNF213 p.R4810K mutation, 114 without RNF213 p.R4810K mutation), 15 acute stroke patients and 33 healthy controls. Cerebral perfusion and collateral circulation were evaluated using pseudo-continuous arterial spin labeling magnetic resonance (pCASL-MRI) and digital subtraction angiography pre-operation and 6 months after operation. Endothelial expression of Cav-1 was verified in the vessel wall of MMD patients by immunofluorescence.We also investigated whether overexpression of Cav-1 affects cell migration and tube formation using human microvascular endothelial cells (HMECs). Results：The serum Cav-1 level of MMD patients intermediated between stroke group and healthy controls. By Suzuki and Takaku’s grades, patients of Grade V presented higher Cav-1 level than that of Grade IV (717.93 ± 311.79 pg/ml versus 487.74 ± 276.2 pg/ml, p<0.05). Interestingly, during the 6 months after operation, patients with better collateral compensation manifested higher post-operative/pre-operative Cav-1 ratio (rCav-1) than bad compensation patients. Cav-1 changes were positively associated with cerebral blood flow in MMD patients using pCASL-MRI (r=0.8615, p<0.0001). Cav-1 was expressed in the endothelial cells of superficial temporal artery of MMD patients. Cav-1 overexpression in HMECs promoted tube formation and cell migration. Conclusions：Our findings suggest that Cav-1 may play a positive role in collateral circulation establishment and cerebral perfusion improvement after bypass surgery in MMD, providing a better understanding of MMD pathophysiology and potential non-surgical targets of MMD.